2020
DOI: 10.1039/c9en01284b
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of silver nanoparticles with antioxidant enzymes

Abstract: Oxidative stress is accepted as a key mechanism of silver nanoparticle (AgNP) toxicity in living organisms. Therefore, mechanistic studies related to the impact of AgNPs on the structure and function of antioxidant enzymes at the molecular level are essential for a comprehensive evaluation of their toxicity. By using a combination of spectroscopic, imaging and fractionation techniques, we explored the interactions between citrate-coated AgNPs (20 nm) and two key antioxidant enzymes: catalase (CAT) and superoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…That was suggested to be related to the formation of AgNPs-CAT complex which in turn resulted in conformational changes in CAT enzyme leading to an impairment of its enzymatic activity. In contrast, the formation of AgNPs-SOD complex has no influence on its enzymatic activity [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…That was suggested to be related to the formation of AgNPs-CAT complex which in turn resulted in conformational changes in CAT enzyme leading to an impairment of its enzymatic activity. In contrast, the formation of AgNPs-SOD complex has no influence on its enzymatic activity [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been established that the activity of antioxidant enzymes strongly depends on the surface properties of AgNPs used in the cytotoxic tests (Barbasz et al, 2017). Recent studies have shown that AgNPs can form complexes with antioxidant enzymes and modify conformational changes in their structures (Liu et al, 2020). Independently of the changes at the cellular level, the surface properties of AgNPs influence the interactions with cell membranes and uptake mechanisms (Ahmed et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of AgNPs is enhanced by PVP-and sodium citrate-coatings (Chen et al 2018). However, risk evaluation can be di cult due to the several AgNPs dissolution mechanisms (Liu et al 2020).…”
Section: Discussionmentioning
confidence: 99%